THE FEATURES OF BURN REGENERATION APPLYING CHITOSAN FILMS IN THE YOUNG ANIMALS - Корнієнко, В.В. (World of Medicine and Biology, 2014)
The aim of our research was to evaluate effectiveness of chitosan films that are applied to treat burns. We studied the features of tissue morphogenesis of the thermal damaged skin in the young animals. We modeled the burn wounds of IIIb degree on the rats of the experimental and control groups. The chitosan films were applied on the animals of the experimental group for the topical treatment. We analyzed the healing of burn wounds by the morphological and cytological criteria. We measured them on 1st, 3rd, 7th, 14th, and 21st days after the burn modelling. Application of the chitosan films to treat thermal burns enhanced wound cleaning from dead tissue and reduced eschar, decreased the intensity of inflammatory reactions and disorders of blood circulation, stimulated the early growth of granulation tissue, and improved epithelialization of the wound.
Keywords: burn; medical supplies; chitosan; morphometry; cytology